EVALUATION OF HERBICIDES PALLAS AND LIMITLESS IN CONTROLLING THE NARROW AND BROAD LEAVE WEEDS WITHIN WHEAT CROP FIELDS AND THEIR EFFECT ON GRAIN YIELD AND IT'S COMPONENTS - Naeem A. Mutlag; A. J. Al-Khaz'ali; K.A. Salman; R. H. Mahdi; T. N. Jaber (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The experiment was conducted at the fields of the Abu Ghraib Research Station's Agricultural Research Department, Ministry of Agriculture during 2018/2019 and 2019/2020 Seasons, this study was aimed evaluation herbicides for controlling narrow and broad weed. The experiment included the use of Pallas OD herbicide, with an application rate of 500 ml. ha-1 and Limitless WG with application rate 400 g. ha-1 + 500 ml. ha-1 activator in addition to free weed treatment and weedy control treatment. A randomized complete block design (RCBD) with three replicates was used. Limitless herbicide treatment achieved the lowest mean number of weeds, which were 1.3 and 2.3 plants. m-2 with a control rate of 93.44% and 91.1%, in comparison to the weedy treatment, it decreased the dry weight of the weed (1.97 and 3.22 g. m-2) with an inhibition rate of 88.46% and 87.1% for the two seasons, respectively, which had the most weeds on average, at 22.67 and 28.7 plants. Throughout the two seasons, the weed plants with the highest average dry weight were 19.12 and 24.86 g. m-2. The number of weeds and plants.m-2 and the control rate were identical between the control treatments using Limitless and Pallas. The number of grains and spikes increased (by 39.2 and 43.20 percent, respectively) with the Limitless therapy. In comparison to the weedy treatment, spike-1 increased grain productivity by 56.9% and 66.47% for both seasons, with a percentage of 32.7% and 36.08%, weight of 1000 grains at a rate of 27.47% and 24.83%. It can be concluded that weed herbicides with low and high concentrations can be used to kill weeds in wheat fields.